Isotopic ratio analysis of cattle tail hair: A potential tool in building the database for cow milk geographical traceability. (15th February 2017) - Behkami, Shima; Zain, Sharifuddin Md.; Gholami, Mehrdad; Bakirdere, Sezgin
Graphical abstract: Highlights: δ 13 C and δ 15 N analysis is used to ascertain the geographical origin of milk/hair. Strong positive correlation between δ 13 C and δ 15 N in milk with that of hair. δ 13 C, δ 15 N of hair used as the basis to build the database for milk traceability. Abstract: The potential for the isotopic ratio analysis of cattle tail hair in determining the geographical origin of raw cow milk in Peninsular Malaysia had been investigated in this research using exploratory visualization. A significant positive correlation (p < 0.0001) (n = 54) was noticed between δ 13 C and δ 15 N in milk with that of hair which indicated that these matrices could be used in tracing the geographical origin of animal produce and tissues, and there is a possibility that hair could be used as a substitute in building the database for the geographical traceability of milk. It was also observed that both hair and milk isotopic ratio correlations exhibited separation between the northern and southern regions. The accuracy of using isotopic ratio in determining geographical discrimination had been clearly demonstrated when several commercial milk samples from the same regions under the study were correctly assigned to the appropriate geographical clusters.